Nukak : ethnoarchaeology of an amazonian people - Kelly, Robert Laurens (2008)
Archaeologists do not value modern ethnographies. Why? Archaeologists need information on material culture – how it is made, who uses it, how long it lasts, what happens when it breaks, what happens when its owner dies, and so on. Although there are some notable exceptions, few modern ethnographies pay attention to such mundane things. But archaeologists need these data to construct arguments that allow us to make secure inferences from the material things that we recover. For this reason, a few archaeologists have climbed out of their trenches and conducted ethnoarchaeological research with the living. Politis is one of those archaeologists, and Nukak is the result of his efforts. This book covers some of the same ground as his 1996 Nukak (published by the Instituto Amazónico de Investigaciones Científicas) but is updated, placed in a larger theoretical context, and made available to the largely monolingual North American audience. The Nukak are a small group of hunter-gatherers who live in the Columbian rain forest. Politis worked with those who were least acculturated to western society. As an archaeologist who has also done ethnographic research, I understand the effort that lies behind Nukak. Ethnography, especially that of nomadic peoples in isolated places, is not easy. There are the usual problems: language barriers, medical issues, feeding yourself and your students, explaining yourself and your task to the people. Párrafo extraído de la reseña a modo de resumen.